Study on the Dynamical Analysis of a Family of Optimal Third Order Multiple-zero Finder (European Journal of Pure and Applied Mathematics, 2023)
We study the complex dynamics by analyzing the dynamical planes associated with the family of third order multiple root finders and the parameter spaces related to the free critical points. The conjugacy maps with the theoretical results of dynamical analysis for the iterative schemes are investigated. In addition, the various experiments are implemented to draw the dynamics of the cubic-order schemes as well as existing methods.
Keywords: conjugacy map; dynamical plane; multiple root; nonlinear equation; parameter space; Blood Rheology model